Review literatur: Pengaruh media booklet dalam edukasi gizi pada pasien malnutrisi - Siska Amelia; Wina Sinaga; Ninik Mudjihartini (Jurnal SAGO Gizi dan Kesehatan, 2024)
Background: Management of malnourished patients involves a process of nutritional counseling and education with the aim of increasing knowledge, food intake and nutritional status to help improve the patient's health.  As a form of non-video media, booklets contain educational material accompanied by graphic illustrations to help understand malnutrition patients.Objectives: This article aims to conduct literature reviews that explains the influence of booklets as a communication medium in the process of nutritional counseling and education and its impact on malnourished patients.Methods: The research design is of literature review on English language articles between 2013-2023, which were published in the most reputable journals in the field of nutrition (Nutrition Science) with the highest H-5 index. Search for articles via the internet from the PubMed database using the keywords malnutrition OR nutrition counseling OR nutrition education OR nutrition communications OR nutrition media OR nutrition booklet. To complete the results data, a search was also carried out for relevant Indonesian language literature to support elaboration and analysis.Results: 26 articles have been obtained discussing topics in the scope of malnutrition, nutritional counseling and education as well as related to the use of booklets as a media for nutritional education. Various previous research results state that selecting communication media and understanding the theory of changing individual health attitudes and behavior is an important part of the nutritional education and counseling process, where medical personnel must be able to build effective communication with malnourished patients. Booklets are a concise and practical communication medium for patients to read again, so they are proven to increase the effectiveness of patients' learning experiences and understandingConclusion: Booklets are an effective non-video media option and have a positive impact on improving the nutritional status of malnourished patients. It is recommended that stakeholders in health sector maximize the use of booklet media in nutritional counseling and education activities to help reduce the problem of malnutrition in Indonesia.